PENGGUNAAN EKSTRAK DAN BUBUK CENGKEH DAN KAYUMANIS UNTUK MEMINIMALKAN KANDUNGAN HISTAMIN PADA IKAN KEMBUNG PEREMPUAN (Rastrelliger neglectus) - Meta Mahendradatta; Adiansyah Adiansyah (Universitas Gadjah Mada, 2008)
In this research, clove and cinnamon were prepared by grinding to produce spice powder and by solvent extraction to produce spice extract. They were stored in plastic and glass jar at ambient temperature for two weeks to observe the change of sensory quality. The spices were then combined and applied to short-bodied mackerel (Rastrelliger neglectus) and the total mesophilic microbes were enumerated. The best concentration of spice combinations which gave the lowest total mesophilic microbe was 2% of clove and 4% and cinnamon in form of powder and 4% of each spice in form of extract. The spice powder and extract, as well, were applied to short-bodied mackerel which has been prepared under various treatments. The treated fishes were stored and the histamine content was analyzed after two hours storage at ambient temperature. The result showed that spice powder and extract could decrease histamine content in short-bodied mackerel processed with and without boiling. Statistic analysis showed that there was significantly difference of each treatment on histamine content (p<0.01). Spice powder in combination with boiling process showed the higher percentage of the decrease of histamine content (94%) than that without boiling (42.5%), spice extract with boiling (28.3%) and without boiling (21%).